Effect of Addition of Two Levels of Urea on Nutritional Value of Molasses Treated Tomato Straw Silage - University of Khartoum, Effect of Addition of Two Levels of Urea on Nutritional Value of Molasses Treated Tomato Straw Silage (Journal of Veterinary Medicine and Animal Production, 2022)
The aim of this study was to determine the nutritive value of tomato straw ensiled for one month with two levels of urea and level of molasses, 0.0% urea +5%molasses (control), 3% urea +5%molasses, and 6% urea +5%molasses. Chemical composition of all treatments was determined by laboratory analysis; an in vitro two stages digestibility was carried out and physical character of the silage have been measured. The data was subjected to analysis of variance using complete randomized design (CRD). The study showed that the final pH was decreased and temperature were increased not significantly (p>0.05) while crude protein was increased significantly (p<0.05) with increase level of urea and due to incubation from 9.8%, 14.21% and 19.3% in the control, 3% and 6% urea after fermentation respectively. While crude fiber, neutral detergent fiber and acid detergent fiber were decreased significantly (p<0.05), acid detergent lignin slightly decreased. The in vitro dry matter, organic matter, crude protein and neutral detergent fiber digestibility were improved significantly (p<0.05) by addition of urea and fermentation. This study concluded that the addition of urea and fermentation improve the nutritive value of tomato straw silages in terms of high protein, low fiber contents and increased digestibility and recommended addition of different levels of molasses and urea in straws silage to improve digestibility. The aim of this study was to determine the nutritive value of tomato straw ensiled for one month with two levels of urea and level of molasses, 0.0% urea +5%molasses (control), 3% urea +5%molasses, and 6% urea +5%molasses. Chemical composition of all treatments was determined by laboratory analysis; an in vitro two stages digestibility was carried out and physical character of the silage have been measured. The data was subjected to analysis of variance using complete randomized design (CRD). The study showed that the final pH was decreased and temperature were increased not significantly (p>0.05) while crude protein was increased significantly (p<0.05) with increase level of urea and due to incubation from 9.8%, 14.21% and 19.3% in the control, 3% and 6% urea after fermentation respectively. While crude fiber, neutral detergent fiber and acid detergent fiber were decreased significantly (p<0.05), acid detergent lignin slightly decreased. The in vitro dry matter, organic matter, crude protein and neutral detergent fiber digestibility were improved significantly (p<0.05) by addition of urea and fermentation. This study concluded that the addition of urea and fermentation improve the nutritive value of tomato straw silages in terms of high protein, low fiber contents and increased digestibility and recommended addition of different levels of molasses and urea in straws silage to improve digestibility.